Beyond professional closure: Uncovering the hidden history of plain accountants - O'Regan, Philip; Killian, Sheila (Accounting, Organizations and Society, 2021)
The received narrative about accounting organisation largely originates from within the walls of the profession, assuming closure, and is not sufficiently informed by an understanding of the actions, experiences and perspectives of those who did not engage in the professional project. Our data offer another perspective, that of the majority of accountants in the field, who prospered for a prolonged period without pursuing strategies of closure or seeking a corporate identity. With a Bourdieusian framing, we explore a rich dataset of almost 3000 individual records from the 1901 and 1911 Irish censuses, supplemented by professional records and trade directories, to examine the diversity of the accounting field in Dublin. Our exploration of this cohort, largely hidden from history, reveals a majority of accountants acting independently in the field, with no strategies to act in concert or to erect occupational barriers to entry. The small minority of accountants pursuing professionalisation came from a background that was already elite. However, in a late colonial context with a weakened state, this broader group of accountants did not present as either excluded or subaltern. Instead, what emerges is evidence of a wider cadre of “Plain” accountants displaying a level of economic progress over a ten-year period that outstrips that of their professionalised peers. Conscious of the ‘imprecision of hierarchies’ in the field (Bourdieu 1988, p. 20), this allows us to consider the role of ‘accountant’ separate from the idea of professional accreditation and to question the seeming inevitability of their conflation.